Poesia e Pantanal: o olhar mosaicado de Manoel de Barros - Gil, Andréia de Fátima Monteiro (2011)
The main objective of this research is to investigate how Manoel de Barros poetry redesigns Pantanal. Especially, it interrogates the space , that is, it questions how the poet s poetry reconfigures Pantanal s geography and how it reorganizes human beings, animals and things, inscribing Pantanal on his poetry. To guide our reflection upon Barros poetic creation, we take studies about poetry into consideration, we examine Pantanal s specifications, we grasp concepts of space from other knowledge areas. We focus our analysis on Livro de pré-coisas, relating it with other works of the poet. As hypothesis, we propose that the poetic language of Manoel de Barros is revealed plural without limits as Pantanal is shown diverse and ambiguous. The research results reinforce that Manoel de Barros (trans) creates Pantanal s space, rearranging it in order to establish a new reality. His poetic language retains mosaic features and stages poetic imagery and sensory words